An Assessment of the Utilization of Diagnostic Parasitology Laboratory Services in Ontario - Harold Richardson; Christine Fleming; Josephine Palmer; Erluo Chen; Robert Lannigan; The Microbiology Committee (Canadian Journal of Infectious Diseases)
OBJECTIVE: Diagnostic parasitology services in Ontario were assessed to determine whether the reduction in the number of provider laboratories from 209 to 70 over the period 1977 to 1994 has affected the availability and quality of service.